Pengaruh Strategi Pemasaran Terhadap Perilaku Konsumen Pada CV. Bintang Keramik di Kota Gunungsitoli 68 (Jurnal Ilmu Sosial Dan Politik, 2025)
This research was conducted at CV. Bintang Keramik in Gunungsitoli City, which sells building materials. This study aimed to determine the influence of marketing strategy on consumer behavior and its extent, using quantitative research methods. Data collection techniques in this study used observation and questionnaires distributed to 41 consumer respondents at CV. Bintang Keramik. The results of this study indicate that Marketing Strategy (X) has a positive and significant effect on Consumer Behavior (Y). This is demonstrated by the results of a simple linear regression test with the equation Y = 10.788 + 0.282 (X), indicating a positive relationship between the variables. The t-test results indicate that the calculated t-value (2.987) is greater than the t-table (1.685). Meanwhile, the sig. value is 0.005 < the 0.05 level of significance. The magnitude of this influence is indicated by the coefficient of determination test of 51.6%. Therefore, this study concludes that Ho is rejected and Ha is accepted.